2019
DOI: 10.1101/779157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-ketoglutarate, an endogenous metabolite, extends lifespan and compresses morbidity in aging mice

Abstract: The decline in early life mortality since the 1950s has resulted in dramatic demographic shift towards aged population. Aging manifests as a decline in health, multiple organ dysfunction and increased vulnerability to diseases, which degrades quality of life. A verity of genetic and pharmacological interventions, mostly from non-vertebrate models, have been identified that can enhance lifespan. Whether these interventions extend healthspan, the disease free and functional period of life, has only sometimes bee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…This study further identified several metabolic pathways that were enriched with metabolites changes, including the sugar and glycerophospholipid metabolism, amino acids, neurotransmitters, and carnitine shuttle [79]. Interestingly, a key tricarboxylic acid cycle (TCA) intermediate metabolite α-ketoglutarate was recently shown to extend lifespan in worms, flies, and mice, which suggested that longevity pathways might be evolutionarily conserved [82][83][84][85].…”
Section: Aging Studies In Model Organismsmentioning
confidence: 83%
“…This study further identified several metabolic pathways that were enriched with metabolites changes, including the sugar and glycerophospholipid metabolism, amino acids, neurotransmitters, and carnitine shuttle [79]. Interestingly, a key tricarboxylic acid cycle (TCA) intermediate metabolite α-ketoglutarate was recently shown to extend lifespan in worms, flies, and mice, which suggested that longevity pathways might be evolutionarily conserved [82][83][84][85].…”
Section: Aging Studies In Model Organismsmentioning
confidence: 83%
“…(B) Glutathione, another antioxidant, is significantly increased in the liver and brain under 30-day fasting. Alpha-ketoglutarate is a tricarboxylic acid cycle (TCA) intermediate that has been linked to longevity in nematodes and mice (18, 19). (C) Nicotinamide is a precursor to NAD + synthesis via a salvage pathway, and increased in the liver but decreased in other tissues in cavefish.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that αKG administration extends the adult lifespan of C. elegans by ATP synthase-TOR axis (Chin et al, 2014). Long-term supplementation of αKG also extends the healthspan in mice by reducing the chromic inflammation (Asadi Shahmirzadi et al, 2020). αKG supplementation also improved the energy expenditure by promoting UCP1 expression (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 97%